Synthesis, characterization, and photodynamic activity of new antimicrobial PVC based composite materials. (5th November 2021) - Thandu, Merlyn M.; Rossi, Giada; Goi, Daniele; Guerriero, Paolo; Poletti, Denise; Strazzolini, Paolo; Comuzzi, Clara
Graphical abstract: Highlights: PVC-based composites as active materials for photodynamic pathogens inactivation. Composition, structure, stability, and bioactivity correlations are discussed. At best, composites kill 10 8 CFU mL -1 of S. aureus after 60 min irradiation. Abstract: Synthesis, chemical, and biological characterization of composite polyvinyl chloride (PVC)-based materials to be applied in the photodynamic inactivation (PDI) of pathogen microorganisms are reported. Different blends of PVC, plasticizers, and photosensitizers have been tested in their photokilling ability vs. Staphylococcus aureus, after irradiation using a multi-LED blue lamp at a fluence rate of 50 W/m 2 . Four common adipates, namely: dibutyl hexanedioate [di(n-butyl) adipate, BA, 1 ], bis(2-ethylhexyl) hexanedioate [bis(2-ethylhexyl) adipate, EA, 2 ], dioctyl hexanedioate (dioctyl adipate, OA, 3 ), and didecyl hexanedioate (dicapryl adipate, DA, 4 ), have been employed in this investigation, in combination with two photosensitizers: 5-(4-carboxy-phenyl)-10, 15, 20-triphenyl-21H, 23H-porphyrin (TPP, 5 ), and the expanded porphyrin 20-(4-carboxyphenyl)-2, 13-dimethyl-3, 12-diethyl-[21]pentaphyrin (PCox, 6 ). The experimental evidence has established the essential role of the addition of a plasticizer to the polymer/photosensitizer mixture in transforming PVC into a photoactive material, being bactericidal properties dependent upon the type and amount of additive. Long-chain linear adipates were found more efficient in imparting the desired bactericidal activity to the final material, reaching in one case the complete abatement of the initial bacterial solution (10 8 CFU/ml) in 60 min. The obtained polymeric films proved to be stable over time and under oxidation conditions; in addition, no release of toxic components was observed over the experiments, definitely demonstrating that the bactericidal action was effectively due to the ROS generated by photosensitizers immobilized into the material. Moreover, SEM and FT-IR analyses proved that no photodegradation of the film took place during the irradiation experiment.